Workaholism, work engagement, and affective commitment: relationships to self-concept levels and work outcomes - Afota, Marie-Colombe; Robert, Véronique; Vandenberghe, Christian (Frontiers in Psychology, 2025)
As a result of the significant changes in businesses around the globe such as the generalization of remote working and digital transformation, the boundaries between work and private life tend to vanish, causing concerns about whether individuals’ investment in their work could have detrimental effects on their life and health. In such context, the notion of heavy work investment, an umbrella construct that subsumes different forms of investment of the self into the work domain, warrants scholarly attention as it may have both a bright and dark side for individuals. The present study focuses on three forms of heavy work investment, i.e., workaholism, work engagement, and affective organizational commitment, and was aimed at examining their association with three levels of the self-concept, i.e., individual, relational, and collective, as well as their contribution to change in number of hours worked, role overload, depression, and emotional exhaustion over time. We conducted a three-wave study with a four-month time separation between measurements among a sample of alumni from a French business school (N = 544) to explore these relationships. Results indicated that as expected, workaholism was positively associated with the individual self-concept, reflecting a tendency to prioritize individual achievements and success, but was also related to a stronger collective self-concept, which involves a self-definition based on group membership. Work engagement and affective organizational commitment were positively and only related to the collective self-concept. In terms of work outcomes, workaholism, but not work engagement and affective commitment, was found to increase the number of hours employees worked across time as well as to heighten their perception of being overloaded by their work. Workaholism was also associated with a significant increase in the odds of depression over time. In contrast, work engagement was found to protect employees from the risk of depression and emotional exhaustion over time. Affective commitment was unrelated to change in any of the four work outcomes. These findings have significant implications for research on heavy work investment and for our understanding of its nature and consequences for employees, which we elaborate on in the discussion.